Data-Efficient Deep Learning Framework for Urolithiasis Detection Using Transfer and Self-Supervised Learning - Jae-Seoung Kim; Sung-Jong Eun (International neurourology journal, 2025)
Purpose: Recent studies on urolithiasis detection using deep learning have demonstrated promising accuracy; however, most rely on large-scale labeled imaging datasets. In clinical practice, only limited and partially labeled computed tomography (CT) scans are typically available, restricting the generalizability of conventional supervised models. This study aimed to propose a data-efficient framework for accurate stone detection from a small CT dataset by integrating self-supervised learning (SSL) and transfer learning (TL). Methods: A total of 100 abdominal CT scans were analyzed and labeled as stone present or normal by expert radiologists. To learn generalizable feature representations from limited data, a SimCLR-based SSL framework with a ResNet50 backbone was employed. During the SSL stage, the model learned from augmented image pairs without labels to maximize similarity between positive pairs and minimize similarity between negatives. The pretrained encoder was subsequently fine-tuned using labeled data in the TL stage, with the lower layers frozen and higher blocks optimized using a linear classifier. Model training was performed with 5-fold cross-validation, and performance was evaluated using accuracy, precision, recall, F1-score, and area under the receiver operating characteristic curve (AUC). Results: The proposed SSL+TL model achieved the best performance (AUC, 0.95; F1-score, 0.91), significantly outperforming both the random initialization and TL-only models. These findings indicate that SSL pretraining effectively learns robust and transferable representations even with limited data. Conclusions: The proposed framework demonstrates the feasibility of artificial intelligence-based urolithiasis detection in small-data clinical environments. Combining SSL and TL alleviates data scarcity and provides a foundation for developing generalizable and resource-efficient diagnostic models for urological imaging. KCI Citation Count: 0